Energy transmission through conjugate heat transfer in arrow-finned double exchanger by executing FEM simulations - Ghazala Ashraf; S. Bilal; Muhammad Ishaq; Khalid Saifullah Syed; A.S. Alqahtani; M.Y. Malik (Case Studies in Thermal Engineering)
Conjugate heat transfer is crucial in enhancing the thermal efficiency of the systems used in power generation, refrigeration and chemical processing industries. Conjugate heat transfer is an interaction of heat conduction within solids and convection in surrounding fluids. The current work is aimed to evaluate the conjugate thermal efficiency of double pipe heat exchanger with arrow shaped fins. The flow is characterized to be laminar, steady and fully developed. The governing model is solved numerically using a finite element method approach. A grid-independence test using h-adaptive technique is performed to guarantee the precision and convergence of numerical procedure. A detailed investigation of the effects of geometrical values such as; conductivity ratio (Ω), number of fins (M), fin height (H∗) and thickness (β), on thermal performance of heat exchanger has been developed. The main performance metrics are the average and equivalent Nusselt numbers and Colburn j-index. The computed data presents that the values of Nusselt number (Nu) rise significantly by increasing the conductivity ratio. For higher arrow fins with H∗=0.4 and 0.6, six arrow fins in number with lager ratio of radii and any conductivity ratio values are suggested for optimum heat transfer coefficient. For H∗=0.8, six arrow fins in number with Ω ≤ 100, and 12 arrow fins in number with Ω ≥5 00 and lager ratio of radii, are recommended. The optimal values of j-index lie at H∗=0.2,Rˆ=0.1 and M = 6 for 1 ≤Ω≤50. For Ω = ∞, the optimal configurations of H∗ = 0.2 with 18 ≤ M≤30, and H∗ = 0.8 with 6 ≤ M≤12 are suggested for j-index.